The Data-Based Self: Self-Quantification and the Data-Driven (Good) Life. - Schüll, Natasha D. (Social Research)
The article focuses on ways in which digital quantification technologies which permeate and exert power on all manner of forms of life. It mentions how quantification serves a neoliberal governmental rationality that accelerates the withdrawal of the welfare state from citizens' lives and ways quantification and algorithmic analysis alienate us from our own practical reasoning, intuition, and understanding of ourselves. It also mentions smartphone apps, data-visualization software, and analytical algorithms, provides an ethnographic entry point and array of devices and apps for monitoring productivity.